Egy paradoxon ígérete: A lírafogalom változása Borbély Szilárd kritikai munkáiban - Pataki, Viktor (Studia Litteraria, 2016)
The critical reviews and articles of Borbély Szilárd are collected in the volume Hungarikum-e a líra? The central question of this book is whether the canonical position of Hungarian poetry is relevant or exists at all. Besides the books of certain authors, this volume inquires into different poetical forms, patterns and modifications in the history of Hungarian poetry, which are subordinated to the ideological discourse, beyond the system of literature. In my study I try to reveal the blindness and insights of Borbély’s reading, and moreover I try to show how the foregoing ideological figure, which Borbély tried to eliminate, can be basically rewritten into Borbély’s concept by the arrestive paradox that constitutes the structures and methods of his book. Hence I attempt to reveal ’Borbély’s unique voice’ that configures the language and narrative technique of his book. My aim was to present the merits of his volume and find its place in the author’s oeuvre.